Mathematical simulation of unsteady three-dimensional processes in the space gas dynamics - Tarnavsky, G.A.; Aultchenko, S.M.; Vshivkov, V.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
The physical, mathematical and computing aspects for simulation of space gas dynamics problems are considered in the paper. The system of Euler gas dynamics equations is used as a basic system of differential equations for the mathematical model. This system is completed by force and energy compositions that simulate the deviation of state equation from ideal one, heat transport processes (such as heat conduction, convection and radiation) and gravitation (point mass gravitation field, distributed gas cloud self-gravitation). The simulation is carried out on the basis of total problem decomposition into a number of individual problems corresponding to various physical processes. The complex computing structure with autonomous segments corresponds to this decomposition. This gives the possibility for expansion and complementability of our computer program system. Some numerical results for shock and wave expansion, gravitational collapse of motionless and revolving gas clouds, gas clot expansion which simulates the formation and explosion of protostars are presented.